2008
DOI: 10.1261/rna.551208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific let-7 microRNA binding complexes in Caenorhabditis elegans

Abstract: Little is known about the protein complexes required for microRNA formation and function. Here we used native gel electrophoresis to identify miRNA ribonucleoprotein complexes (miRNPs) in Caenorhabditis elegans. Our data reveal multiple distinct miRNPs that assemble on the let-7 miRNA in vitro. The formation of these complexes is affected but not abolished by alg-1 or alg-2 null mutations. The largest complex (M*) with an estimated molecular mass of >669 kDa cofractionates with the known RISC factors ALG-1, VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…The variety of observations specific to C. elegans let-7 in this work and those of Vella et al (2004a,b) indicate that this may be a particularly complex microRNA in the diversity of its interactions and functions. Consistent with this possibility are studies in which specialized RNA (Cevec et al 2010) and RNP complexes (Chan et al 2008) have been observed in association with this microRNA. let-7 is a highly conserved microRNA, with substantial (and somewhat consistent) diversity in both seed and non-seed regions.…”
Section: Discussionsupporting
confidence: 54%
“…The variety of observations specific to C. elegans let-7 in this work and those of Vella et al (2004a,b) indicate that this may be a particularly complex microRNA in the diversity of its interactions and functions. Consistent with this possibility are studies in which specialized RNA (Cevec et al 2010) and RNP complexes (Chan et al 2008) have been observed in association with this microRNA. let-7 is a highly conserved microRNA, with substantial (and somewhat consistent) diversity in both seed and non-seed regions.…”
Section: Discussionsupporting
confidence: 54%
“…Gel filtration has been used to fractionate cell extracts from C. elegans , Drosophila, and human cells to determine the sizes of complexes corresponding to RNAi activity, siRNAs, miRNAs, or miRNP/RISC (Caudy et al , 2002, 2003; Chan et al , 2008; Gregory et al , 2005; Pham et al , 2004). Gel filtration can also be used to detect cofractionation of proteins of interest with miRNAs or to purify fractions that possess miRNA-related activities, that is miRNA binding or pre-miRNA processing.…”
Section: Rationale Methods and Materialsmentioning
confidence: 99%
“…Although ALG-1 probably acts with miRNAs to control the division axis, it remains unclear which miRNAs are involved. Recent studies identified large numbers of high-confidence miRNA-mRNA interactions, which are associated with various biological processes (Chan et al, 2008;Zhang et al, 2007;Zisoulis et al, 2010). Genetic confirmation of such interactions is hampered by redundancies between miRNAs and, in general, by the modest inhibition of target genes by individual miRNAs (Baek et al, 2008;Inui et al, 2010).…”
Section: Alg-1 Provides Multiple Developmental Functionsmentioning
confidence: 99%